Evaluation of the efficacy of lycopene gel compared with minocycline hydrochloride microspheres as an adjunct to nonsurgical periodontal treatment: A randomised clinical trial - Aya Ali; Saif Saliem; Ali Abdulkareem; Hani Radhi; Sarhang Gul (Elsevier, 2021)
Background/purpose: The prescription of antibiotics as an adjunct to mechanical periodontal therapy in patients with severe periodontitis is recommended; however, the side effects of antibiotics are a major concern. The aim of this study was to evaluate the efficacy of lycopene (Lyc) antioxidant gel versus minocycline hydrochloride microspheres (ARISTIN) as an adjunct to the nonsurgical treatment of periodontitis. Materials and methods: Three identical periodontal pockets/patient received root surface debridement followed by the random application of either ARISTIN, Lyc, or placebo gel (control, Ctrl). Clinical parameters, plaque index, bleeding on probing, probing pocket depth, and clinical attachment loss, were recorded at the baseline and after 30 days. Additionally, the levels of interleukin-8 (IL-8), matrix metallopeptidase 9, and tissue inhibitor of metalloproteinases 1 (TIMP1) in gingival crevicular fluid samples were assessed at the same time points. Results: Twenty-three patients with periodontitis completed the study. Both ARISTIN and Lyc treatments showed significantly greater gains in attachment (1.94 ± 1.33 and 1.72 ± 0.88, respectively) than the Ctrl treatment (1.04 ± 0.96). Compared with those in the Ctrl, only ARISTIN showed a significant reduction in IL-8 level, whereas TIMP1 levels were significantly upregulated in the Lyc gel and ARISTIN sites. The effect size estimation indicated that Lyc gel exhibited considerably greater efficacy than the Ctrl gel. Conclusion: Lyc gel and ARISTIN offer almost equal improvement in both clinical and biochemical parameters of periodontitis.